DAMPAK PEMBANGUNAN PERKEBUNAN KELAPA SAWIT TERHADAP TINGKAT PENDIDIKAN MASYARAKAT DI DESA SUMBER JAYA KECAMATAN SIAK KECIL - Ade Wulandari; Henny Indrawati; Almasdi Syahza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted to determine the impact of the oil palm plantations on the education level of the community in Sumber Jaya Village. The research population is people who have oil palm plantations (farmers) and live in Sumber Jaya Village, amounting to 166 people. The sample was determined by using purposive sampling technique, so that a sample of 117 people who met the criteria was obtained. The data collected consisted of land area, educational level of children produced by farmers, expenditure and income of farmers using questionnaires and documentation. The data collected were analyzed by finding the development of oil palm plantations. Have the impact of chi square analysis. Research result on the level of education. Based on the result of the analysis with the help of the SPSS program, it is known that the chi square value is 114,054 sig 0,000 and the chi square value Table 77,93.Key Words: Oil palm plantation, level of education